Endoscopic butterfly graft myringoplasty in small to medium perforation in adolescent chronic otitis media: our experience in 15 cases - Mogre, Dilesh A.; Ahmed, Fazal M.; Banu, Parvathi T. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic otitis media is one of the most common paediatric conditions but ear surgery in children is challenging. The high rates of failure have often questioned surgical management of dry asymptomatic perforations in pediatric age group. This study aimed to assess the results of butterfly cartilage myringoplasty in adolescent population with small to medium perforation in chronic otitis media. Methods: We studied 15 cases in our prospective cross sectional observational study performed in the department of ENT at a secondary health centre in the eastern suburbs of Mumbai between October 2016 and September 2017. Children aged between 12 to 18 years with chronic otitis media mucosal inactive type with a central, small to medium sized tympanic membrane perforation and mild to moderate conductive hearing loss were included in this study. Results: Results showed that the average age was 14.63 (SD=1.79 years) with an M: F ratio of 1:1.14. The mean hearing gain in cases with medium perforation was 11.75 dB and 5.7 dB in cases having small perforations two cases showed residual crescentic perforation. Conclusions: Our study shows that endoscopic butterfly graft myringoplasty in small to medium perforation in adolescent age group has good success rate and is safe, quick and minimally invasive day care procedure.